Odpowiedzi

2010-02-08T15:09:26+01:00
A) 7x + 3y + 6x + 2 = 13x+3y+2= -65+9+2= -52
b) 8 + 4z + 6x + 10z=8+14z+6x=8+14*(-1)+6*(-5)=8+(-14)+(-30)=-36
c) 7x + 3y + 8x + 9y=15x+12y=15*(-5)+12*3= -75+36= -39
d) -5x + 3y -3z + 10= -5*(-5)+3*3-3*(-1)+10= 25+9+3+10=47
2010-02-08T15:09:30+01:00
A) 7x + 3y + 6x + 2 = 13x+3y+2=13*(-5)+3*3+2=-65+9+2=-54
b) 8 + 4z + 6x + 10z = 8+14z+6x=8+14*(-1)+6*(-5)=8-14-30=-36
c) 7x + 3y + 8x + 9y = 15x+12y= 15*(-5)+12*3=-75+36=-39
d) -5x + 3y -3z + 10 = -5*(-5)+3*3-3*(-1)+10=25+9+3+10=47
2010-02-08T15:15:44+01:00
A)7x + 3y + 6x + 2 =13x+3y+2=13*(-5)+3*3+2=-65+9+2=-54
wartość liczbowa -54
b) 8 + 4z + 6x + 10z=8+14z+6x=8+14*(-1)+6*(-5)=8-14-30=-36
wartość liczbowa -36
c)7x + 3y + 8x + 9y =15x+12y=15*(-5)+12*3=-75+36=-39
wartość liczbowa -39
d)-5x + 3y -3z + 10=-5*(-5)+3*3-3*(-1)+10=25+9+3+10=47
wartosć liczbowa 47